Changemakers share their why, collaborate as critical friends, and highlight leadership skills - Rebekka J. Jez; Christopher Dennis; Michelle Coleman; Corné Conradie; Abongile Matyaleni; Diana Ramirez; Chanté Rezandt; Kayla Wilkins; Cassie Herndon (AOSIS, 2023)
Background: Changemakers are justice-minded individuals working toward implementing positive and sustainable change within their communities. Aim: The project created a space for Changemakers to connect, engage in critical dialogue, and leave with shared knowledge and skills to dismantle oppressive, deficit-based educational systems in the aftermath of COVID-19. Setting: From October 2021 to June 2022, 18 American and South African Changemakers from primary, secondary, and higher education institutions exchanged messages about their regional context and attended the Changemaker Symposium in South Africa. Method: This qualitative study examined how the Changemaker framework guided educators to frame [ubuntu], convene [masikhule], and ignite change [skep verandering]. They framed the strengths and challenges in their regions. Teams convened to address challenges using assets-based ideas that oppose deficit thinking and allow them to become leaders who ignite agency to ignite systemic change. The individual and group narratives were collected via open-ended questions, group discussions, and written artifacts. Results: They developed statements on: exploring reasons for teaching, collaborating with critical friends, and developing critical leadership skills. A phenomenological analysis of the narratives examined commonalities within each Changemakers' lived experience. Conclusion: Findings indicate that this process allowed participants to collaborate and reimagine ways to inspire others while renewing their commitment to the responsibilities they face as educators affected by the pandemic. Contribution: From this project, educators have a framework to participate in global discourse that illuminates commonalities through critical friendships, decreases burnout, humanizes their experiences and increases the implementation of culturally responsive and sustaining inclusive practices.